2022
DOI: 10.1111/ecc.13563
|View full text |Cite
|
Sign up to set email alerts
|

The role of telehealth in oncology care: A qualitative exploration of patient and clinician perspectives

Abstract: Objective: The COVID-19 pandemic has accelerated the rapid expansion of telehealth, affording opportunities to study its impact on oncology care. Our qualitative study explored physician and patient perspectives of telehealth in cancer care.Methods: Semistructured interviews were conducted with seven physicians and eleven patients, recruited from an Australian hospital oncology department. Two authors independently coded the transcripts with emerging themes identified and refined iteratively in a thematic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…(19) The removal of a patient's support system and the added disadvantages of telehealth limiting physicians' ability to physically provide support in the form of touch and non-verbal communication of empathy, negatively impact the psychosocial well-being of cancer patients. (4,14) Providers in this study perceived that in consideration of the psychosocial factors that both in uence and arise from cancer pain, telehealth cannot fully replicate the human interaction that is required to provide "good quality comfort care" (C10) to patients with cancer pain. Given these ndings, there may be a bene t in providing cancer pain management through a hybrid of both virtual and in-person care.…”
Section: Discussionmentioning
confidence: 98%
“…(19) The removal of a patient's support system and the added disadvantages of telehealth limiting physicians' ability to physically provide support in the form of touch and non-verbal communication of empathy, negatively impact the psychosocial well-being of cancer patients. (4,14) Providers in this study perceived that in consideration of the psychosocial factors that both in uence and arise from cancer pain, telehealth cannot fully replicate the human interaction that is required to provide "good quality comfort care" (C10) to patients with cancer pain. Given these ndings, there may be a bene t in providing cancer pain management through a hybrid of both virtual and in-person care.…”
Section: Discussionmentioning
confidence: 98%
“…Some untrained participants in other studies were also tentative to try video calls as they felt video may interfere with vital first impressions and rapport, as the technology might fail, or waste valuable relationship building time. 13,35 The 'home visit' context of community palliative care is mostly soft skills based, whereas telehealth is a mix of 'hard' technical skills and 'soft' communication skills, such as developing rapport remotely which requires focus, intention and practice. 27,41 To adapt to telehealth, health professionals need to consider how they can transition their in-person rapport skills while maintaining technology and patient-centred care in telehealth.…”
Section: Discussionmentioning
confidence: 99%
“… 7 10 Furthermore, telehealth has the potential to improve access to palliative care and enable more equitable distribution of limited healthcare resources. 11 13 However, palliative care professionals prefer in-person interactions 7 , 9 and have expressed concerns that the remoteness of telehealth represents a barrier to care delivery and rapport building. 14 , 15 Along with these concerns, health professionals want education and evidence-based telehealth guidelines to ensure a compassionate, person-centred approach to care is not lost when using telehealth.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers wanted improvements in telehealth consultation scheduling and administration 28 . Others have reported that the support telehealth administrators provide consumers to access video consultations is highly valued, 33 but few studies have examined consumers' opinions on how telehealth consultations are scheduled. We identified technology and system barriers such as a clinician's telephone number not being displayed on the consumer's telephone, virtual waiting rooms where consumers cannot interact with administrators, and scheduling consultations with large windows of time.…”
Section: Discussionmentioning
confidence: 99%